A study of help seeking behavior of psychiatric patients - Pradhan, SN; Sharma, SC; Malla, DP; Sharma, R (Journal of Kathmandu Medical College, 2014)
Background: A large number of mentally ill patients prefer to visit non-medical practitioners such as faith healers becauseof the stigma attached to mental illness and/or belief that mental illness are caused by supernatural powers. Faith healersare more convenient to be approached fi rst because of ease of availability and prevalent cultural belief and persuasion. Objective: The current study aims to fi nd the help seeking behavior of patients suffering from mental illness and whomthey approach fi rst once affected, either psychiatrists or faith healers. Methods: A cross sectional study was conducted among patients admitted in the psychiatric ward of Kathmandu MedicalCollege Teaching Hospital during 1st January to 30th July 2012. All patients admitted in the ward during that period wereinformed about the purpose of the study and a written informed consent was taken. In case of psychotic patients, theconsent was obtained from nearby relatives. Results: Among 54 patients enrolled in the study, signifi cant number of psychotic patients (n=15) visited faith healersin comparison to only 4 non-psychotic patients. Number of females (n=12) visiting faith healers in comparison to males(n=7) was higher. Patients having belief in black magic were more likely to visit faith healers than those who were nonbelievers.In contrary to the popular belief, patients approaching the faith healers spent more money (>20) in the treatment thanwho approached psychiatrists (<20). Conclusion: The study shows that most of the patients suffering from mental illness prefer to approach faith healers fi rstbecause of the prevailing trust on faith healers, because they are locally available and because of a prevailing belief insupernatural causation of mental illness. DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10538 Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013: 21-24